The responses of neurons in the temporal cortex of primates, and face identification and detection. - Rolls, E; Tovee, M; Purcell, D; Stewart, A; Azzopardi, P (Springer Science+Business Media, 1994)
The ability of a human observer to detect the presence of a briefly flashed picture of a face can depend on the picture's spatial configuration, that is on whether its features are rearranged (jumbled) or are in their normal configuration. The face-detection effect (FDE) is found under conditions of backward masking, when the presence of a face can be detected with shorter masking intervals when it is in the normal than when in the rearranged configuration. A similar effect is found when the subject is asked to classify the face as rearranged or not - the face-classification effect (FCE). Part of the interest of the FDE and the FCE is that they show how the configuration of a stimulus can be an important factor in the perceptual processing which leads to detection and classification of the stimulus. To analyse these effects we recorded from single neurons in the cortex in the superior temporal sulcus of macaques when they were shown (in a visual fixation task) normal and rearranged faces under backward masking conditions shown in experiments 2 and 3 to produce, with the same apparatus, the FCE, and also to produce comparable effects on the identification of which face was present (called hereafter the face-identification effect), and also of the clarity of the face. We found in experiment 1 that there are some face-selective neurons which respond to faces only, or better, when the features in the faces are in their normal configuration rather than rearranged. We also showed in this experiment that the difference in the response to the normal as compared to the rearranged faces became greater when the masking stimulus was delayed more. Thus, at intermediate delays, there are more neurons active for the normal than for the rearranged face. We therefore propose that the FDE, the FCE, and the face-identification effect arise because the total number of neurons activated by faces in their normal configuration is greater than that activated by rearranged faces, because of the sensitivity of some face-selective neurons to the spatial arrangement of the features. The experiments also show that backward visual masking does produce abrupt termination of the firing of neurons in the temporal cortical visual system, so that the duration of a neuronal response is very short when visual stimuli can just be perceived.